A 数字时代汉语国际传播在Instagram上教学的视觉修辞研究——以《丝合汉语》为列 - Yu, Zhang; Tela, Irvan Aditya (Bambuti | Fakultas Bahasa dan Budaya Universitas Darma Persada, 2025)
日益发展的数字时代改变了人类的生活方式，其中尤为明显的一个变化在于交流的形式。语言作为交流媒介是人类在各个领域进行互动的主要工具。在过去，研究者们对汉语国际发展和传播策略的研究都颇具丰富，然而对国际社交媒体的关注却仍显不足。《丝合汉语》作为一所汉语教学机构，充分证明了国际社会对汉语的高度关注。《丝合汉语》拥有192千粉丝，通过基于Instagram社交媒体的图片和短视频来推广和传播国际汉语教学。因此，要通过Instagram上的图片和教学视频来了解汉语国际传播的过程，有必要将视觉修辞分析作为桥梁。通过视觉修辞的分析，可以更深入地了解基于数字化理念的汉语国际传播的发展流程，以及观察汉语国际传播的过程中所采用的国际汉语教学和营销策略的背后结构。 The growing digital age has transformed the way humans live, with one of the most significant changes being in the realm of communication. Language, as a medium of communication, serves as the primary tool for human interaction across all fields. Historically, researchers have conducted extensive studies on the international development of the Chinese language and communication strategies. However, there remains a notable lack of focus on international social media platforms. SilkChinese, a Chinese language teaching organization, exemplifies the global interest in the Chinese language. With 192,000 followers, SilkChinese leverages Instagram to promote and disseminate Chinese language education through pictures and short videos. To comprehend the process of international Chinese language dissemination via Instagram, it is essential to employ visual rhetoric analysis. This approach enables a deeper understanding of the development of international Chinese language communication in the digital age and provides insights into the structure and strategies behind international Chinese language teaching and marketing.